2019
DOI: 10.18502/cmm.4.4.382
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effect of the bark and root extracts of Punica granatum on oral Candida strains isolated from liver recipients

Abstract: Background and Purpose: Oral candidiasis is one of the most common fungal infections in humans. The treatment and prophylaxis of the patients suffering from this infection require the identification of new anti-Candida agents with no side effects or toxicity like medicinal plants. The present study was conducted to compare the antifungal activities of the aqueous, ethanolic, and methanolic extracts of the bark and roots of P. granatum with those of two routine antifungal agents (i.e., fluconazole and nystatin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…It is used in folk medicine to treat various diseases such as ulcers, fever, diarrhea, and microbial infections ( Endo et al, 2010 ). In addition, different parts of P. granatum , such as the leaves, flowers, and seeds, have antimicrobial, antioxidant, and antifungal properties ( Lavaee et al, 2018 ). The antifungal activity of Punica granatum extract has already been reported against some species of Candida ( Anibal et al, 2013 ; Mansourian et al, 2014 ; Akroum, 2017 ; Paul et al, 2018 ) and against dermatophyte fungi ( Foss et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is used in folk medicine to treat various diseases such as ulcers, fever, diarrhea, and microbial infections ( Endo et al, 2010 ). In addition, different parts of P. granatum , such as the leaves, flowers, and seeds, have antimicrobial, antioxidant, and antifungal properties ( Lavaee et al, 2018 ). The antifungal activity of Punica granatum extract has already been reported against some species of Candida ( Anibal et al, 2013 ; Mansourian et al, 2014 ; Akroum, 2017 ; Paul et al, 2018 ) and against dermatophyte fungi ( Foss et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lavaee et al . compared the efficacy of the methanolic and ethanolic extracts of the bark and roots of Punica in the isolation of Candida species and found that the methanolic extracts were more effective [ 38 ]. Accordingly, in the current study, ethanolic extracts were used.…”
Section: Discussionmentioning
confidence: 99%
“…The treated Petri dishes were placed at 4°C for 1-2 hours and then incubated for 48 hr at 37°C. Nystatin 0.2 mg/ml was used as the reference drug [ 27 ]. At the end of the period, the inhibition zones formed on the media were measured with a transparent ruler in millimeters.…”
Section: Methodsmentioning
confidence: 99%